Media and Advertising Preferences of Nepalese Audiences - Thapa, Gopal (Journal of Advanced Academic Research, 2017)
No one can escape from death, tax and advertising. There are various media available for advertising. Advertising is used by different organization in different ways. Different customers have responded differently, to the different message and media. This article highlights on the consumers’ preference towards the message and media on the basis of age, gender and education. This study is part of the pilot study of my PhD research work. It is a descriptive study based on survey method. Total 80 respondents consisting different gender, age and education background were taken as sample on judgmental basis. The result revealed that most of the Nepalese prefer television, television advertising and musical message.